Cancer of the gastroesophageal junction: a diagnosis, classification, and management review - Chevallay, Mickael; Schmidt, Thomas (Annals of the New York Academy of Sciences, 2018)
Management of gastroesophageal junction (GEJ) adenocarcinoma is a controversial topic. The rising incidence of this cancer requires a clear consensus to ensure proper management. Application of oncological principles for tumors of the esophagus or stomach is not possible because of comparative differences in the biology of GEJ adenocarcinoma, leading to different therapeutic options. Staging work-up with endoscopy, endosonography, and PET is essential to inform the choice of neoadjuvant treatment and surgical approach to GEJ adenocarcinoma. Surgery remains the only curative treatment and should be undertaken in specialized centers.
Gesehen am 25.04.2019